The new Asian Hemisphere : the irresistible shift of global power to the East - MAHBUBAN, Kishore (New York : Publick Affairs, 2008)
Tells what may be on the agenda as Western domination ends and the Asian renaissance impacts world politics, markets and history.
Includes bibliography and index